An Optical Heterodyne Technique for Dynamic Eddy-Current Damping Force Evaluation - P. Youplao; Akihiro Takita; Hadi Nasbey; S. Mitatha; Yusaku Fujii (IEEE Transactions on Instrumentation and Measurement, 2021)
This work presents and discusses a method for evaluating a dynamic eddy-current damping (ECD) force that is automatically generated in response to eddy currents induced within a conductive plate while moving across a magnetic field in relative motion to a nearby stationary magnet. In the experiment, a Doppler shift frequency signal between the optical interference fringe frequencies was used to calculate the velocity of the moving conductive plate. The other relevant mechanical quantities acting on the plate, such as the displacement, acceleration, and resultant force, were then evaluated by performing numerical calculations of the velocity. Finally, the evaluation of the ECD force could be achieved by performing a calculation to remove the frictional force component from the resultant force. Furthermore, an approximation analysis used to calculate the value of the ECD force was proposed and compared with the measured value as well. From the experimental results, the combined standard uncertainty for evaluating the ECD force was approximately 3.57 mN, corresponding to 3.13% of the maximum eddy-current force of approximately 114.0 mN.
Keywords: Non-Destructive Testing Techniques; Magnetic Properties and Applications; Structural Health Monitoring Techniques